Thermodynamic and economic investigation of a screw expander-based direct steam generation solar cascade Rankine cycle system using water as thermal storage fluid. (1st June 2017) - Li, Jing; Li, Pengcheng; Gao, Guangtao; Pei, Gang; Su, Yuehong; Ji, Jie
Highlights: Combination of DSG, cascade SORC and water-based storage is innovative. Optimum operating temperature of steam screw expander ranges below 250 °C. Thermo-economic comparison between direct and indirect systems is made. Compared with oil-based system, DSG system is more efficient. Cost of steel is less than one-third of the oil's. Abstract: Solar electricity generation system (SEGS) which employs cascade steam-organic Rankine cycle (SORC) and steam screw expander (SE) is promising due to the high efficiency at moderate heat source temperature. This paper puts a special emphasis on heat storage and thermo-economic evaluation. Preferable operating temperature of the system is first clarified on the basis of SE characteristics. The temperature-dependent permissible stress of steam accumulator is modelled and the capital cost is investigated. Comparison between the direct steam generation (DSG) SEGS and an indirect one using thermal oil is made at a power capacity of 1 MW and storage of 6.5 h. The results indicate the DSG system has both thermodynamic and economic superiorities. The hot side temperature ( T H ) of SORC generally does not exceed 250 °C to achieve an optimum solar thermal power efficiency. Given radiation of 750 W/m 2, the maximum efficiency ( η T, m ) is 14.3% with a corresponding T H around 240 °C. The material cost of pressure vessels is 2.55 million RMB. For the indirect system, the optimal T H is about 230 °C and η T, m approximates to 13.2% and the estimated oil cost is 7.92 million RMB. It is recommended to adopt steam accumulators in the SE-driven SEGS.